Design Thinking Ethics of Neighboring Life Inspiration of Prophet's Hadith - Nisarohmah, Lutfiana (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the ethical value of being a neighbor. This research method employs a qualitative kind through library studies and field studies with a design thinking hadith approach. The results and discussions of this study include the ethic of neighboring life, the Prophet’s exemplary inspiration of a neighboring life, and the ethical development innovation in a neighboring life. This study concludes that the hadith has an inspiring message to foster the ethic of living next door through simple things to create harmony for human life.